Unexplained massive pulmonary embolism in acromegaly patient: A case report - Usamah Al‐Anbagi (14778037) (2024)
Key Clinical Message Our case highlights the importance of recognizing acromegaly as a potential risk factor for venous thromboembolism (VTE). Despite a thorough thrombophilia workup yielding unremarkable results, further research is warranted to elucidate the underlying mechanisms linking acromegaly and thrombophilia. This understanding will aid in improving risk assessment and management strategies for patients with acromegaly. Acromegaly, a rare disorder characterized by excessive growth hormone secretion, is associated with various comorbidities including hypertension, diabetes mellitus, and obstructive sleep apnea. While previous studies have identified abnormalities in hemostatic factors in acromegaly patients, the association between acromegaly and venous thromboembolism (VTE) remains poorly understood. We present the case of a 36‐year‐old male with a history of acromegaly who presented with acute dyspnea, chest pain, and cough. Despite a prior trans‐sphenoidal hypophysectomy, his acromegaly symptoms persisted. Upon evaluation, he was found to have bilateral pulmonary embolism. Thorough thrombophilia workup was unremarkable, suggesting acromegaly as a potential risk factor for VTE. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.8867